2013
DOI: 10.1080/07347324.2013.747313
|View full text |Cite
|
Sign up to set email alerts
|

Important Factors of Early Addiction Recovery and Inpatient Treatment

Abstract: Research is needed that confirms inpatient treatment outcomes and evaluates patient typologies. Factors of early recovery and inpatient treatment are examined to (1) support inpatient treatment effectiveness research, (2) explore impacts on outcomes of patient differences (collegiate vs. traditional), and (3) learn about factors that influence inpatient treatment effectiveness. Overall, 95 of 149 (63.8%) participants were classified as progressing in readiness for change from pre to post treatment. Second, a M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…Initial studies found that higher levels of RTC upon Downloaded by [University of Wyoming Libraries] at 17:38 18 September 2013 entering outpatient treatment were significantly associated with treatment outcomes at 1-and 3-year follow-ups (Project MATCH Research Group, 1997, 1998. Another study found that baseline levels of RTC have a significant effect on positive changes in treatment and recovery-related outcome variables (hope, resiliency, family functioning, and craving) over the course of residential treatment (Shumway, Bradshaw, Harris, & Baker, 2013). Most research however, in outpatient and inpatient settings, has found either modest or no significant association between initial levels of RTC and posttreatment outcomes (DiClemente et al, 2004;Gossop, Stewart, & Marsden, 2007;Hewes, 1998).…”
Section: Readiness For Change and Treatmentmentioning
confidence: 91%
See 1 more Smart Citation
“…Initial studies found that higher levels of RTC upon Downloaded by [University of Wyoming Libraries] at 17:38 18 September 2013 entering outpatient treatment were significantly associated with treatment outcomes at 1-and 3-year follow-ups (Project MATCH Research Group, 1997, 1998. Another study found that baseline levels of RTC have a significant effect on positive changes in treatment and recovery-related outcome variables (hope, resiliency, family functioning, and craving) over the course of residential treatment (Shumway, Bradshaw, Harris, & Baker, 2013). Most research however, in outpatient and inpatient settings, has found either modest or no significant association between initial levels of RTC and posttreatment outcomes (DiClemente et al, 2004;Gossop, Stewart, & Marsden, 2007;Hewes, 1998).…”
Section: Readiness For Change and Treatmentmentioning
confidence: 91%
“…With regard to program type, we expect that traditional participants (older) will have a higher likelihood in progressing in RTC than collegiates (younger), being that collegiates may experience greater precontemplative thinking upon entering treatment and show lower increases in treatment outcomes than traditionals (Shumway et al, 2013).…”
Section: Summary and Hypothesesmentioning
confidence: 99%
“…This finding has been evident in research where collegiate populations tend to have higher means on selfreport instruments with less change being reported over time (Shumway, Bradshaw, Harris, & Baker, 2013). According to the research cited, collegiateage participants report fewer negative symptoms and more positives.…”
Section: Assessment Of Change In Hope and Copingmentioning
confidence: 50%
“…Though we are not sure what accounts for this finding, we do note that collegiate participants/clients (most often younger) appear to be less impacted and less insightful about their predicament and the future consequences of their SUD. Unlike many collegiate participants, noncollegiates have a longer history of wreckage, more people counting on them, and fewer people to bail them out of their difficulty (Shumway et al, 2013). This makes hope a little more fleeting in the early recovery process and perhaps is a more realistic assessment of the problem often seen with collegiate participants.…”
Section: Assessment Of Change In Hope and Copingmentioning
confidence: 87%
“…However, despite evidence supporting the relative success of combinations of biopsychosocial interventions, multiple studies have suggested as many as 80-90% of individuals recovering from addiction-related disorders relapse within Sally Wasmuth, Jeffrey L Crabtree, and Patricia J Scott the first year of recovery (Bart 2012, Shaffer et al 2004, with others suggesting that 60% of persons in recovery are dissatisfied with treatment and therefore discontinue services (Shumway et al 2013).…”
Section: Addiction-as-occupationmentioning
confidence: 99%